2022
DOI: 10.3847/1538-4357/ac5e36
|View full text |Cite
|
Sign up to set email alerts
|

The Simons Observatory: Galactic Science Goals and Forecasts

Abstract: Observing in six frequency bands from 27 to 280 GHz over a large sky area, the Simons Observatory (SO) is poised to address many questions in Galactic astrophysics in addition to its principal cosmological goals. In this work, we provide quantitative forecasts on astrophysical parameters of interest for a range of Galactic science cases. We find that SO can: constrain the frequency spectrum of polarized dust emission at a level of Δβ d ≲ 0.01 and thus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 233 publications
0
8
0
Order By: Relevance
“…We note that these forecasts are different with respect to the ones presented in Hensley et al (2022), as the two forecasts are drawn from two different catalogues employing different kind of sources, molecular clouds with size larger than 1 pc from Miville-Deschênes et al (2017). Reassuringly however, both methods lead to a similar expected number of detections in intensity at 280 GHz: 12,000 cold clump detections in this work and 8500 in Hensley et al (2022).…”
Section: Forecasts For Somentioning
confidence: 65%
See 1 more Smart Citation
“…We note that these forecasts are different with respect to the ones presented in Hensley et al (2022), as the two forecasts are drawn from two different catalogues employing different kind of sources, molecular clouds with size larger than 1 pc from Miville-Deschênes et al (2017). Reassuringly however, both methods lead to a similar expected number of detections in intensity at 280 GHz: 12,000 cold clump detections in this work and 8500 in Hensley et al (2022).…”
Section: Forecasts For Somentioning
confidence: 65%
“…The lower noise levels and finer angular resolution of the SO survey will also better resolve any substructure in the cold clumps, in both intensity and polarization. Hensley et al (2022) previously presented forecasts for the number of similar molecular clouds that SO will resolve in polarization, highlighting this fact. These resolved studies will allow us to expand our understanding of the magnetic field structure of cold clumps and relationship to their surrounding filaments and molecular clouds.…”
Section: Conclusion/summarymentioning
confidence: 89%
“…Furthermore, our analysis is restricted to only the section of the Stream that intersects the BICEP/Keck region. Extending the sky area to include the entire Stream, running the RHT on forthcoming H I emission data from the Galactic Australian Square Kilometre Array Pathfinder Survey (Dickey et al 2013) with 30″ angular resolution, and using higher angular resolution dust polarization data (Hensley et al 2022;CMB-S4 collaboration et al 2022;CCAT-Prime collaboration et al 2023) are all possible extensions of this work that can improve the sensitivity of this method for detecting or setting limits on dust polarization from the Stream.…”
Section: Polarized Dust In Magellanic Stream Imentioning
confidence: 99%
“…We also measure the SED of the dust correlated with H I filaments. Knowledge of the dust SED is essential for CMB studies (Chluba et al 2017;Hensley & Bull 2018) and for providing constraints for physical models of dust composition (e.g., Hensley et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…New, high spatial resolution observations of the polarised dust emission that probes the entire line of sight through the SMC, using forthcoming instruments such as the Prime-cam (CCAT-Prime Collaboration et al 2023) and the Simons Observatory (Hensley et al 2022), similar to the few other nearby galaxies observed with the Stratospheric Observatory for Infrared Astronomy (SOFIA) Highresolution Airborne Wideband Camera Plus (HAWC+ Jones et al 2020;Lopez-Rodriguez et al 2022), can be compared with our H filament orientation map (Figure 6). This will test whether the magnetic alignment of H filaments persists through the full SMC volume.…”
Section: Polarised Starlight and Dust Emission Of The Smcmentioning
confidence: 99%